Decoding the Genomic and Functional Landscape of Emerging Subtypes in Ovarian Cancer - Micoli, Giulia; Lavikka, Kari; Li, Yilin; Pirttikoski, Anna; Afenteva, Daria; Senkowski, Wojciech; Marchi, Giovanni; Vähärautio, Anna; Muranen, Taru A.; Joutsiniemi, Titta; Hietanen, Sakari; Virtanen, Anni; et al. (American Association for Cancer Research (AACR), 2026)
Ovarian high-grade serous carcinoma (HGSC) is characterized by pervasive genomic instability and high inter- and intra-tumor heterogeneity. Approximately half of HGSC tumors harbor homologous recombination deficiency (HRD), rendering them vulnerable to PARP inhibitors and platinum-based chemotherapy. In contrast, patients lacking HRD (HR-proficient, HRP) generally respond poorly to current therapies. To overcome heterogeneity and identify relevant HGSC subtypes, we characterized the genomic landscape of 640 tumors from 243 patients using whole-genome sequencing. Our chromosomal instability signature–based analysis characterized the structural variation landscape and revealed five HGSC subtypes, validated in an independent dataset. Two HRD subtypes, associated with BRCA1- or BRCA2-driven alterations, demonstrated favorable treatment responses. Strikingly, three HRP subtypes emerged, marked by unique structural alterations and gene expression patterns, tumor microenvironment interactions, and different chemotherapy responses. Notably, organoid experiments showed subtype-specific sensitivity to CHK1 inhibition, suggesting prexasertib as a potential targeted treatment for most currently untreatable HRP patients.